Experimental Handling Challenges Result in Minor Changes in the Phagocytic Capacity and Transcriptome of Head-Kidney Cells of the Salmonid Fish Coregonus maraena - Martorell-Ribera, Joan; Koczan, Dirk; Tindara Venuto, Marzia; Viergutz, Torsten; Brunner, Ronald M.; Goldammer, Tom; Gimsa, Ulrike; Rebl, Alexander (Frontiers in Veterinary Science, 2022)
Aquaculture management involves regular handling procedures, but these can evoke stress responses in farmed fish. We compiled an extensive list of published parameters that indicate the most likely handling-induced physiological deviations from the norm. However, since these parameters are based almost exclusively on studies of rainbow trout and Atlantic salmon, we conducted a handling-challenge experiment with maraena whitefish (Coregonus maraena). This salmonid fish was sampled at either 3 or 24 h after a single 1-min handling or after 10 days of daily repeated 1-min handling. The cortisol levels were strongly elevated in some individuals at 3 h after the single handling challenge, but these elevations were not significantly different between the challenged and control cohorts. The phagocytic capacity of myeloid head-kidney cells stimulated with fluorophore-labeled, inactivated Aeromonas salmonicida was significantly decreased in maraena whitefish at 3 h after the handling challenge compared to control fish. Microarray analysis of head-kidney samples from the challenged and control fish revealed 12 differentially expressed genes at 3 h and 70 at 24 h after the single handling episode, but only 5 differentially expressed genes after 10 days of repeated daily handling. The identified genes were assigned to numerous stress- and immune-relevant functional pathways, including “glucocorticoid receptor signaling” (3 h post-challenge), “HIF1A signaling” (24 h post-challenge), or “complement system” (10 days of repeated challenge). Our data reveal the tight interconnection of immune and stress pathways in the head kidney of maraena whitefish and corroborate several parameters previously found regulated in other tissues of handling-stressed rainbow trout. These findings indicate that handling may compromise the health and welfare of maraena whitefish in aquaculture.